Using public interest litigation for tobacco control: Insights from India - Jagdish Kaur; Arvind Vashishta Rinkoo; Ranjit Singh (Wolters Kluwer Medknow Publications, 2017)
The Indian notion of "Public Interest Litigation (PIL)" represents a moral and humane process for providing justice to an individual or a group in matters relating to infringement of fundamental rights or denial of civil privileges. The goal of PIL in India is to counter governmental lawlessness, administrative deviance, and exploitation of disadvantaged groups by denying them their rights and entitlements. Although this paper selectively describes the use of the PIL mechanism for ensuring implementation of large graphic health warnings on packages of tobacco products in India, there is a sufficient published literature to corroborate the successful use of this mechanism in India in different tobacco control settings. In fact, over the years, this legal tool has allowed the tobacco control community in India, to extensively promote human rights approach to tobacco control. In the wake of growing interference of tobacco industry worldwide, this paper explores PIL as a potent and effective tool for claiming public health rights related to tobacco control. The PIL has considerable potential to be used for enforcement of tobacco control measures and for stopping tobacco industry from engaging in activities which are detrimental to the health of the people at large. It is important to continuously identify potential avenues through which lessons and recommendations pertaining to PIL could be incorporated into the WHO Framework Convention on Tobacco Control implementation plans and guidelines, with special focus on different intercessional mechanisms that are available from time to time. To set the ball rolling, the authors suggest two such avenues.